2016
DOI: 10.1016/j.yexcr.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of human islet stellate cells

Abstract: Similar to our previous rat experiment, the current study shows that human islets also contain ISC which is phenotypically similar but not identical to human PSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 38 publications
2
27
0
1
Order By: Relevance
“…Our previous studies have confirmed the presence of stellate cells within the islets (ISCs), which are identical in the expression of retinoid-containing fat droplets [51,52,53,54,55]. A loss of oil red O-stained fat droplets was associated with the activation of diabetic ISCs, and we speculate whether the transfer of lipid droplets from the inside to the outside of the ISCs leads to local fat deposition and the inhibition of normal β-cell function.…”
Section: Discussionsupporting
confidence: 67%
“…Our previous studies have confirmed the presence of stellate cells within the islets (ISCs), which are identical in the expression of retinoid-containing fat droplets [51,52,53,54,55]. A loss of oil red O-stained fat droplets was associated with the activation of diabetic ISCs, and we speculate whether the transfer of lipid droplets from the inside to the outside of the ISCs leads to local fat deposition and the inhibition of normal β-cell function.…”
Section: Discussionsupporting
confidence: 67%
“…We found that insulin secretion from islets cocultured in vitro with db/m mouse ISCs was significantly increased compared to that from islets cocultured with ISCs from db/db mice. Subsequent iTRAQ protein screening of the ISCs showed that both ISCs cultured under static conditions and their supernatants showed high Wnt5a protein expression compared with diabetic ISCs [24][25][26][27][28][29][30]. e mechanisms leading to ISCs quiescence play an important role in regulating islet function via the Wnt5a-Fzd5 system and can help us understand the crosstalk between cells inside the islets of Langerhans and serve as a target for the prevention of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…But their proliferation and migration rates were significantly lower than typical PSCs. Recently, Zha et al (2016) used standard explants techniques to isolate the corresponding ISCs in human pancreatic tissue, which were also different from the typical PSCs. Human ISCs express α-SMA, desmin, vimentin and GFAP, as well as collagen I, collagen III and fibronectin.…”
Section: Islet Stellate Cells (Iscs)mentioning
confidence: 99%
“…Islet stellate cells can act as subgroups of PSCs and interact with pancreatic β-cells, included enhancing β-cell apoptosis, inhibiting proliferation, and decreasing β-cell function, which are important in islet fibrosis and islet cell dysfunction ( Li et al, 2016 ; Zha et al, 2016 ).…”
Section: Islet Stellate Cells (Iscs)mentioning
confidence: 99%